2016
DOI: 10.1136/jim-2016-000142
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Klotho and Fibroblast Growth Factor 23 Levels in Diabetic Nephropathy with Different Stages of Albuminuria

Abstract: The relationship between soluble Klotho (s-Klotho) levels, fibroblast growth factor 23 (FGF23) levels, and albuminuria in patients with diabetic chronic kidney disease (CKD) remains unclear. A total of 109 patients with type 2 diabetes (mean age 61.63±9.77 years), at the outpatient clinic of the Antalya Research and Training Hospital Nephrology Unit between January and June 2014, as well as 32 healthy controls (mean age 49.53±7.32 years) were enrolled for this cross-sectional study. Patients were classified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
(30 reference statements)
2
22
1
Order By: Relevance
“…We further found out that in the Hp 2-2 genotype, α -klotho renal expression is gradually reduced with the progression in CKD stages, and this decrease is more prominent in the diabetic state. This association is in agreement with previous studies that have shown that renal α-klotho gene expression is regulated by pathophysiological conditions including hypertension, diabetes, and chronic renal failure in animal models and in humans [ 16 , 17 , 20 , 29 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further found out that in the Hp 2-2 genotype, α -klotho renal expression is gradually reduced with the progression in CKD stages, and this decrease is more prominent in the diabetic state. This association is in agreement with previous studies that have shown that renal α-klotho gene expression is regulated by pathophysiological conditions including hypertension, diabetes, and chronic renal failure in animal models and in humans [ 16 , 17 , 20 , 29 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have indicated that renal α-klotho gene expression is regulated by pathophysiological conditions including long-term hypertension, oxidative stress, diabetes, and chronic renal failure in both animal models and humans [ 16 , 17 , 20 , 29 32 ]. Hence, we evaluated whether the increased renal iron deposits associated with the Hp 2-2 genotype also affect the α -klotho renal expression both in DN mice and patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is still debated whether soluble or full-length KL serves as an antiaging hormone, since a receptor for soluble KL has not been identified to date (27). Additionally, a recent paper suggests that soluble KL only acts with fibroblast growth factor 23 (FGF23) and serves as a circulating FGF23 coreceptor, but has no FGF23-independent functions (27,28). The aging suppressor protein KL binds to the fibroblast growth factor receptor and maintains serum phosphate levels within normal range by increasing renal phosphate excretion (29).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistently, the present study showed that, after adjustment for GFR (accurately determined by Tc 99m -DTPA clearance) as well as for Ca and P, the association between serum FGF23 levels and the presence of LEAD remained statistically significant. Recent studies suggested that higher levels of FGF23 are associated with diabetic nephropathy [30, 31]. In consideration of the influence of kidney function on serum FGF23 levels, the present study only enrolled subjects with normal kidney function (serum creatinine <115 µmol/L and GFR  ≥ 60 mL/min/1.73 m 2 ).…”
Section: Discussionmentioning
confidence: 99%